2010
DOI: 10.1017/s0950268810001445
|View full text |Cite
|
Sign up to set email alerts
|

A school outbreak of pandemic (H1N1) 2009 infection: assessment of secondary household transmission and the protective role of oseltamivir

Abstract: In mid-June 2009, an outbreak of pandemic (H1N1) 2009 (pH1N1) infection occurred in a secondary school in Hong Kong. We carried out an epidemiological investigation to delineate the characteristics of the outbreak, gauge the extent of secondary household transmission, and assess the protective role of oseltamivir in household contacts. We interviewed pH1N1-confirmed cases using a standardized questionnaire. Sixty-five of 511 students in the school were affected. Of the 205 household contacts identified, 12 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 4 publications
(6 reference statements)
1
37
0
1
Order By: Relevance
“…18,41,46,47 Three studies utilized active surveillance systems for recruitment, 29,41,48 while seven studies recruited index cases and their households following specific local outbreaks in schools or summer camps. 18,23,24,28,30,34,42 Most studies were conducted very early in the pandemic; twelve studies (44%) did not recruit cases after June 2009 (eFigure 1, http://links.lww.com). Only 7% (2/27) of studies were published before January 2010.…”
Section: Resultsmentioning
confidence: 99%
“…18,41,46,47 Three studies utilized active surveillance systems for recruitment, 29,41,48 while seven studies recruited index cases and their households following specific local outbreaks in schools or summer camps. 18,23,24,28,30,34,42 Most studies were conducted very early in the pandemic; twelve studies (44%) did not recruit cases after June 2009 (eFigure 1, http://links.lww.com). Only 7% (2/27) of studies were published before January 2010.…”
Section: Resultsmentioning
confidence: 99%
“…This result is broadly consistent with household studies showing higher susceptibility in children than in adults. 23,[82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] We are aware of only one study that has identified statistically significant age-specific differences in infectivity, 83 suggesting that this effect is less pronounced. Although our analysis indicates a higher reproduction number in children, it is important to recognize that this result is partly a consequence of age-specific mixing patterns coupled with greater susceptibility in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…18 Household secondary-attack-rate estimates were 9% for influenza-like illness in a spring 2009 outbreak in Texas 24 and 6% for confirmed pH1N1 infection in an early summer 2009 outbreak in Hong Kong. 23 Two analyses of influenza-like illness among the household contacts of children involved in an outbreak of pH1N1 in a New York City school estimated secondary attack rates of 18% 15 and 11%, 22 which fall within the 4%–23% range for US households. 8 …”
Section: Discussionmentioning
confidence: 99%
“…Outbreaks of pH1N1 in the US have been reported for a summer camp, 19 households, 2,3,8,20–24 and schools. 15,17,23,25,26 The CDC provides guidelines for the management of outbreaks of pH1N1 in many settings, including camps. 27 This report describes the transmission of pH1N1 among the participants of a youth camp and their household contacts, as well as the effect of age on susceptibility to symptomatic disease.…”
mentioning
confidence: 99%